Results of complex treatment of diabetic retinopathy - N. G. Zavgorodnyaya; S. V. Mikhalchik (Zaporozhye State Medical University, 2014)
Aim. To investigate the results of complex treatment of diabetic retinopathy. Methods and results. Diabetic retinopathy (DR) is a late complication of diabetes mellitus (DM), which leads to severe disability and significantly reduces the quality of life of patients. In the DR peroxidation of proteins with decreased antioxidant activity is enhanced in the blood of patients. These findings point to the desirability of placing products containing short carotenoids into the complex therapy of diabetic patients with DR in order to maintain visual function. Conclusion. In the DR under the influence of short carotenoids in complex treatment decreased severity of microvascular complications, increased total retinal lability by 8-16 Hz on the average are noted, the level of electrical retinal sensitivity phosphene threshold decreased to 87 uA (p <0.05), photosensitivity of the retina increased by 16 dB on the average, the amount of relative scotomas reduced.